Biochemical composition and volatile profile analysis of three varieties of Coffea arabica and their correlation with the microclimate of Mount Tangkuban Perahu, West Java, Indonesia - ROSY ANNAZA FIRNABILLAH; ERI MUSTARI; ERLY MARWANI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Firnabillah RA, Mustari E, Marwani E. 2024. Biochemical composition and volatile profile analysis of three varieties of Coffea arabica and their correlation with the microclimate of Mount Tangkuban Perahu, West Java, Indonesia. Biodiversitas 25: 3264-3276. The quality of coffee is determined by various biochemical compounds, including chlorogenic acid, caffeine, trigonelline, sucrose, and oil, as well as the volatile metabolite profile in coffee beans. Genetic factors and environmental conditions at the coffee cultivation site influence the composition of these compounds. This study aimed to analyze the biochemical composition and volatile profile of various coffee samples, including Ateng, Tim-Tim, and Sigarar Utang, and investigate their correlation with microclimate factors. Different analytical methods were used to examine the green beans, including High-Performance Liquid Chromatography-Mass Spectrometry (HPLC-MS) for caffeine, chlorogenic acids, sucrose, and trigonelline, Soxhlet methods for oil content determination, and Gas Chromatography-Mass Spectrometry (GC-MS) for volatile compound analysis. The results showed distinct biochemical components and metabolite profiles among the three arabica coffee varieties. The Ateng variety had the highest concentrations of chlorogenic acid, while the Tim-Tim variety had the lowest content of these compounds. Trigonelline and caffeine content was similar across all varieties. Sucrose content was highest in the Sigarar Utang variety, while oil content was higher in the Ateng and Tim-Tim varieties compared to Sigarar Utang. Principal Component Analysis (PCA) showed significant metabolite variation among the three varieties, with PC1 and PC2 accounting for 69.2% of the variance. Furthermore, Partial Least Squares-Discriminant Analysis (PLS-DA) successfully distinguished the three varieties and identified potential biomarker compounds for classification. Additionally, the study discovered that the environmental factor, specifically light intensity affected the sucrose and oil compounds in arabica green beans coffee. The study concluded that the three varieties' biochemical composition and volatile metabolites differed. Certain compounds were found to correlate with measured microclimatic factor.